Relación entre los bifosfonatos y la osteonecrosis: una revisión sistemática y un protocolo de metanálisis - Ramos Pazmiño, Brigitte Anabel (2025)
Introduction: Currently, bisphosphonates are a group of drugs with an inhibitory mechanism focused on bone tissue resorption by osteoclasts. They show comforting results in terms of improving the quality of life of patients with this type of disease or bone alterations, as they are highly effective in reducing bone metastasis and pain. Bisphosphonate - associated osteonecrosis is a necrotic bone located in the maxillofacial area with a persistence of more than eight weeks after a patient starts taking bisphosphonate medication and with the insufficiency of head and neck radiation therapy. Objective: To design protocols for the prevention, during administration and after treatment of osteonecrosis with bisphosphonates. Methods: The study was descriptive in scope, qualitative in approach and explanatory in nature to collect and compile current theoretical considerations on the use of bisphosphonates and osteonecrosis. Results: The literature review allowed the establishment of meta - analysis protocols for pathology with intravenous bisphosphonates before and during the first 3 months of treatment, during administration and after treatment, as well as protocols for pathology with oral bisphosphonates before and after administration of oral treatment; cases of patients with or without risk factors and; protocols with established osteonecrosis. Conclusions: Despite the fact that the appearance of osteonecrosis in the maxillofacial area is unlikely, the use of bisphosphonates in a rational manner and based on a premature diagnosis is inherent to avoid extreme pain, which subsequently has repercussions on the quality of life of individuals.